Associations between environmental tobacco smoke exposure and oral health symptoms in adolescents - Na-Young Yoon; Il Yun; Yu Shin Park; Eun-Cheol Park (BMC, 2022)
Abstract Background Oral health condition in adolescence impacts the oral well-being throughout life. This study aimed to determine the association between environmental tobacco smoke (ETS) exposure and oral health in adolescents, using nationally representative data. Methods Using data from the 2020 Korea Youth Risk Behavior Web-based Survey, we assessed self-reported data on ETS exposure and oral health symptoms in 37,591 non-smoking adolescents. The dependent variables were self-reported oral health symptoms of adolescents (tooth fracture, dental pain, and gum bleeding). ETS exposure was the primary independent variable. Chi-square tests and multivariable logistic regression analyses were performed to examine these relationships. Results ETS exposure was positively associated with oral symptoms compared to no-ETS exposure in adolescents [boys, odds ratio (OR) 1.56, 95% confidence interval (CI) 1.46-1.66; girls, OR 1.50, 95% CI 1.41-1.60]; individuals with good oral health habits such as frequent tooth brushing [boys, three times or more a day, OR 1.38, 95% CI 1.24-1.53] and less soda consumption [girls, less than once a day, OR 1.73, 95% CI 1.29-2.33] had a weaker association. ETS exposure was positively associated with dental pain [boys, OR 1.55, 95% CI 1.45-1.66; girls, OR 1.50, 95% CI 1.41-1.60] and gum bleeding [boys, OR 1.43, 95% CI 1.29-1.58; girls, OR 1.32, 95% CI 1.21-1.44]; however, tooth fracture was significantly associated only in girls [OR 1.28, 95% CI 1.13-1.45]. Conclusions ETS in various environments is negatively associated with oral health in adolescents. This association could vary depending on health habits. Sophisticated policies to protect South Korean adolescents from ETS can be developed from these findings.